Fostering Active Ageing Through Participatory Social Interaction Education in Bolon Village - Wahyuni, Endang Sri; Arifiati, Retna Febri (Poltekkes Kemenkes Surakarta, 2025)
Background: The ageing population in Indonesia necessitates proactive interventions to maintain the quality of life among older adults, particularly in terms of social interaction, which often declines due to isolation, stigma, and mobility limitations. This community engagement initiative aimed to enhance the understanding and participation of older adults in social interaction through a community-based educational program entitled “I am an Active and Happy Older Adult”. Methods: The intervention was conducted in Bolon Village on Saturday, September 13, 2025. The activity was carried out in three stages, namely (1) preparation, which included coordination with village officials, needs analysis, and the preparation of materials and leaflets; (2) implementation in the form of face-to-face health counseling using leaflets and interactive discussions; and (3) evaluation using the pre-post counseling method. The evaluation was conducted by administering a structured questionnaire containing ten closed-ended questions before and after counseling to 41 respondents (35 elderly people, six elderly health cadres, and other participants) to assess changes in their level of knowledge. Results: The majority of participants were aged 60–74 years (73.2%), female (78%), and had low educational backgrounds (71.1% ≤ junior high school). There was a significant increase in the mean understanding score from 4.95 (pre-test) to 9.56 (post-test), accompanied by a decrease in standard deviation from 0.865 to 0.502, indicating a more uniform level of understanding among participants following the intervention. Conclusion: These findings demonstrate that culturally responsive and participatory health education is effective in increasing awareness among older adults regarding the importance of social interaction. Follow-up evaluation, capacity strengthening of community health cadres, and expansion of interventions targeting older and male participants are recommended to realize the principles of active ageing inclusively and sustainably.